Cloning and heterologous expression of a novel subgroup of class IV polyhydroxyalkanoate synthase genes from the genus Bacillus. Issue 1 (2nd January 2017) - Mizuno, Kouhei; Kihara, Takahiro; Tsuge, Takeharu; Lundgren, Benjamin R; Sarwar, Zaara; Pinto, Atahualpa; Nomura, Christopher T
Abstract: Many microorganisms harbor genes necessary to synthesize biodegradable plastics known as polyhydroxyalkanoates (PHAs). We surveyed a genomic database and discovered a new cluster of class IV PHA synthase genes ( phaRC ). These genes are different in sequence and operon structure from any previously reported PHA synthase. The newly discovered PhaRC synthase was demonstrated to produce PHAs in recombinant Escherichia coli .